2022
DOI: 10.1039/d2cp01230h
|View full text |Cite
|
Sign up to set email alerts
|

Full-dimensional quantum studies of vibrational energy transfer dynamics between H2O and Ar: theory assessing experiment

Abstract: We report the first full-dimensional quantum mechanical calculations of ro-vibrational inelastic scattering dynamics between water molecules and argon atoms on an accurate potential energy surface, using a recently developed time-independent...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…Recently, we reported an exact full-dimensional quantum scattering algorithm 22 and the corresponding code (ABC + D) 23 for ro-vibrationally inelastic scattering between a triatom and an atom based on the time-independent close-coupling (TICC) approach. This method has been applied to the H 2 O− He 24 and H 2 O−Ar 25,26 systems, and the latter case showed a satisfactory agreement with known experimental vibrational quenching rate coefficients. This progress also presents the opportunity to conduct benchmark tests on the applicability of the RR approximation to inelastic scatterings involving triatomic molecules.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…Recently, we reported an exact full-dimensional quantum scattering algorithm 22 and the corresponding code (ABC + D) 23 for ro-vibrationally inelastic scattering between a triatom and an atom based on the time-independent close-coupling (TICC) approach. This method has been applied to the H 2 O− He 24 and H 2 O−Ar 25,26 systems, and the latter case showed a satisfactory agreement with known experimental vibrational quenching rate coefficients. This progress also presents the opportunity to conduct benchmark tests on the applicability of the RR approximation to inelastic scatterings involving triatomic molecules.…”
Section: Introductionmentioning
confidence: 58%
“…29 The resulting root-meansquare fitting error of this PES is only 0.284 cm −1 , which shows high fitting fidelity. For the quantum scattering calculations, we used our recently developed ABC + D code 23 based on the algorithm reported in our previous work, 22,26 where state-tostate transition probabilities P E ( )…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To directly compare with the experimental data, [163][164][165] the rate coefficients for the combined stretching fundamental state were obtained by Boltzmann averaging those for (1, 0, 0) and (0, 0, 1) states. At room temperature, T = 295 K, our calculated rate coefficient (1.52 Â 10 À13 cm 3 s À1 molecule À1 ) 167 is in very good agreement with the experimental value of (1.4 AE 0.2) Â 10 À13 cm 3 s À1 molecule À1 by Finzi et al 163 However, for the (0, 2, 0) initial state, Finzi et al reported a value of (4.2 AE 0.9) Â 10 À13 cm 3 s À1 molecule À1 at the room temperature, 163 which is over five times larger than our value of 7.8 Â 10 À14 cm 3 s À1 molecule À1 . 164 Our calculated results are significantly lower than the upper limit of Zittel and Masturzo 165 for both initial states.…”
Section: H 2 O + Rgmentioning
confidence: 91%
“…[163][164][165] Recently, the vibrational energy transfer dynamics for H 2 O in collision with Ar was theoretically investigated for the first time by employing the new 3 + 1 TICC method 81 on a new and accurate PES based on high-level ab initio data, 166 yielding state-to-state cross sections and rate This journal is © the Owner Societies 2023 coefficients. 167,168 We note that this newly developed PES still lacks an accurate description in the long range. As a result, the current version of the PES is not suitable for applying to cold collisions.…”
Section: H 2 O + Rgmentioning
confidence: 99%